Haploinsufficiency of the Primary Familial Brain Calcification Gene SLC20A2 Mediated by Disruption of a Regulatory Element. Issue 8 (7th June 2020) - Cassinari, Kévin; Rovelet‐Lecrux, Anne; Tury, Sandrine; Quenez, Olivier; Richard, Anne‐Claire; Charbonnier, Camille; Olaso, Robert; Boland, Anne; Deleuze, Jean‐François; Besancenot, Jean‐François; Delpont, Benoit; Pouliquen, Dorothée; et al.
Abstract: Objective: Primary familial brain calcification (PFBC) is a rare cerebral microvascular calcifying disorder with diverse neuropsychiatric expression. Five genes were reported as PFBC causative when carrying pathogenic variants. Haploinsufficiency of SLC20A2, which encodes an inorganic phosphate importer, is a major cause of autosomal‐dominant PFBC. However, PFBC remains genetically unexplained in a proportion of patients, suggesting the existence of additional genes or cryptic mutations. We analyzed exome sequencing data of 71 unrelated, genetically unexplained PFBC patients with the aim to detect copy number variations that may disrupt the expression of core PFBC‐causing genes. Methods: After the identification of a deletion upstream of SLC20A2, we assessed its consequences on gene function by reverse transcriptase droplet digital polymerase chain reaction (RT‐ddPCR), an ex vivo inorganic phosphate uptake assay, and introduced the deletion of a putative SLC20A2 enhancer mapping to this region in human embryonic kidney 293 (HEK293) cells by clustered regularly interspaced short palindromic repeats (CRISPR) ‐ CRISPR‐associated protein 9 (Cas9). Results: The 8p11.21 deletion, segregating with PFBC in a family, mapped 35 kb upstream of SLC20A2 . The deletion carriers/normal controls ratio of relative SLC20A2 mRNA levels was 60.2% ( P < 0.001). This was comparable with that of patients carrying an SLC20A2 premature stop codon (63.4%; P < 0.001). The proband exhibited a 39.3% decrease of inorganic phosphate uptake in blood ( P = 0.015). In HEK293 cells, we observed a 39.8% decrease in relative SLC20A2 mRNA levels after normalization on DNA copy number ( P < 0.001). Discussion: We identified a deletion of an enhancer of SLC20A2 expression, with carriers showing haploinsufficiency in similar ranges to loss‐of‐function alleles, and we observed reduced mRNA levels after deleting this element in a cellular model. We propose a 3‐step strategy to identify and easily assess the effect of such events. © 2020 International Parkinson and Movement Disorder Society